Field releases of Diadegma semiclausum helen against diamondback moth, Plutella xylostella L., of crucifers in Benguet and Mountain Province - Cardona, E. V.; Morallo-Rejesus, B.; Inocencio, E. L.; Bansiong, M. L.; Eusebio, J.E. (1996)
Field releases of Diadegma semiclausum, a larval parasitoid supplemented with selective insecticides (Bacillus thuringiensis kurstaki and Teflubenzuron), significantly reduced the popu-lation of diamondback moth (DBM), Plutella xylostella, in cabbage growing areas of Benguet and Mountain Province.

Utilization of D. semiclausum by farmers in Atok reduced their frequency of insecticide application from 32 to only 8 during dry season and from 16 to only 5 times during wet season (1990). An increase in yield and net income of 9 % and 17 %, respectively, was realized. In 1995, 70 % of the farmers in five municipalities of Benguet were utilizing D. semiclausum supplemented with 3-6 sprayings/season to control DBM.

Dispersal of D. semiclausum was recorded at 6 km away from the release sites with average parasitism of 84 %. In 1995, this parasitoid was collected from 47 of 50 release sites in Benguet Province and from 14 of 15 release sites in municipalities of Mountain Province where average parasitism of 65 % and 59 %, respectively, was noted.
Keywords: Pesticide research; Cabbage diseases and pests